DEIXIS ANALYSIS IN "THE GIFT OF THE MAGI" FOR TEACHING WRITING NARRATIVE - Maulida Fortuna Uzma; Yoga Prihatin; Fajar Prihatini (PROJECT (Professional Journal of English Education), 2022)
The aims of this research are to identify the types of deixis, to analyze the reference meaning, and to find out the application in teaching writing narrative. This research was conducted by using a descriptive qualitative method. In addition, analyze three types of deixis in short story using Yule's theory. The data which used short story “The Gift of the Magi”, meanwhile the data were obtained from documentation. The result of this results: 1) There were 216 deixis, those are 185 (86%) person deixis, 10 (4%) spatial deixis, and 21 (10%) temporal deixis. 2) Most of reference meaning refers to Della and Mr. James because main character in this short story is Della and Mr. James, 3) Deixis can be applied in teaching writing narrative in KD 3.5 & 4. 5 about identifying the linguistic and social aspects of narrative texts & capturing meaning contextual related to a social function, structure text, and linguistic elements of the narrative. Keywords:  Deixis, Reference, Short Story, Writing, Narrative